2004
DOI: 10.1002/arch.20018
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of G proteins in Lepidopteran cell lines: Partial sequences of six G protein alpha subunits

Abstract: The aim of this work was to sample the diversity of G protein alpha subunits in lepidopteran insect cell lines. Here we report the amplification by degenerate PCR of partial sequences representing six G protein alpha subunits from three different lepidopteran insect cell lines. Sequence comparisons with known G protein alpha subunits indicate that the Sf9, Ld and High Five cell lines each contain (at least) one Galpha(q)-like and one Galpha(i)-like Galpha subunit. All six PCR products are unique at the nucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…It has been suggested that olfactory receptor signaling might proceed via a G-protein mediated secondary messenger system (Rützler and Zwiebel, 2005). Again this system did not require the addition of any G␣ proteins suggesting that endogenous G␣ proteins expressed by Sf9 cells are able to couple to ORs (Knight and Grigliatti, 2004). It is also possible that insect ORs might not transduce signals through G proteins, as a recent report suggested that two Drosophila ORs adopt a different conformation to that of GPCRs (Benton et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…It has been suggested that olfactory receptor signaling might proceed via a G-protein mediated secondary messenger system (Rützler and Zwiebel, 2005). Again this system did not require the addition of any G␣ proteins suggesting that endogenous G␣ proteins expressed by Sf9 cells are able to couple to ORs (Knight and Grigliatti, 2004). It is also possible that insect ORs might not transduce signals through G proteins, as a recent report suggested that two Drosophila ORs adopt a different conformation to that of GPCRs (Benton et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…Most likely, this is a weak but hardly productive interaction of hH 4 R with insect cell G-proteins that becomes unmasked in the presence of GAIP. Since RGS proteins do not interact with G s , the observed interaction can only be due to G q -or G i -like proteins that both are present in Sf9 cells [44].…”
Section: Page 22 Of 38mentioning
confidence: 98%
“…Therefore, we chose to utilize the a 2A -AR and Ga i1 and Gb 1 g 2 proteins expressed in the Sf 9 insect cell/baculovirus expression system, which has been characterized previously [20]. Additionally, we incorporated a urea extraction step into the existing method of a 2A -AR membrane preparation in order to greatly reduce or eliminate all endogenous G-proteins (Ga and Gbg) from the insect cell membranes as demonstrated previously [20,22,23]. Using [ 3 H]MK912 binding to a 2A -AR/Sf9 membranes, we found that the K d ranged between 0.5 Á/1.0 nM (this compares to a Kd of 1.25 nM for previously reported data [24] and the B max was between 5Á/20 pmol/mg, with /95% specific binding using yohimbine as the antagonist.…”
Section: Resultsmentioning
confidence: 99%